Genetic Variations in Bilirubin Metabolism Genes and Their Association with Unconjugated Hyperbilirubinemia in Adults. (12th December 2016) - Chiddarwar, Ashish S.; D'Silva, Selma Z.; Colah, Roshan B.; Ghosh, Kanjaksha; Mukherjee, Malay B.
Summary: Objective : The present study was undertaken to investigate the genotype and allele frequencies of the variants in the four bilirubin metabolism genes ( UGT1A1, OATP2, HMOX1, and BLVRA ) and their association with hyperbilirubinemia.Material and Methods : Genotyping of 17 genetic variants was performed in 115 adults with hyperbilirubinemia and 150 controls by PCR‐RFLP, GeneScan analysis, and direct DNA sequencing.Results : Genetic polymorphisms of the UGT1A1 promoter, specifically the T‐3279G phenobarbital‐responsive enhancer module and (TA)7 dinucleotide repeat, as well as the intron and coding region variants of the OATP2, HMOX1, and BLVRA genes, were significantly higher among the cases than the controls. Further, nearly 82% of the cases showed the presence of significantly four or more variants as compared to 37% of the controls ( P < 0.0001) and the mean total serum bilirubin levels also increased according to the number of variants co‐expressed.Conclusions : This study demonstrates that polymorphisms in the bilirubin metabolism genes had a significant effect on bilirubin levels and could be genetic risk factors for hyperbilirubinemia.